2009
DOI: 10.3168/jds.2008-1937
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-term effects of omitting two weekend milkings on the lactational performance and mammary tight junction permeability of dairy ewes

Abstract: The long- and the short-term effects of omitting 2 milkings weekly in early (wk 8 to 14) and mid lactation (wk 15 to 22) were investigated in an experiment conducted with a total of 58 dairy ewes (40 Manchega and 18 Lacaune). Ewes submitted to 2 milking omissions were milked twice daily from Monday to Friday (0800 and 1800 h), and once daily on Saturday and Sunday (1600 and 1400 h, respectively). Individual data were collected for milk yield (weekly), milk composition (biweekly), and somatic cell count (SCC; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
3
2
2
1
Order By: Relevance
“…East Friesian crossbred, Manchega, Sicilo-Sarde) and small-cisterned ewes that resembled unselected or non-dairy sheep. The percentages of Najdi's cisternal milk (55% and 67% during suckling and milking periods, respectively) were similar to the percentages reported in Manchega ewes (Rovai et al, 2002;Castillo et al, 2009), East Friesian crossbred dairy ewes (McKusick et al, 2002b) and Sicilo-Sarde dairy ewes (Ayadi et al, 2011). On the other hand, the percentages of cisternal milk in the current study were lower than those percentages in Lacuane (74-77%, Rovai et al, 2002;Castillo et al, 2009) and Sarda ewes (82%, Nudda et al, 2000).…”
Section: Discussionsupporting
confidence: 69%
“…East Friesian crossbred, Manchega, Sicilo-Sarde) and small-cisterned ewes that resembled unselected or non-dairy sheep. The percentages of Najdi's cisternal milk (55% and 67% during suckling and milking periods, respectively) were similar to the percentages reported in Manchega ewes (Rovai et al, 2002;Castillo et al, 2009), East Friesian crossbred dairy ewes (McKusick et al, 2002b) and Sicilo-Sarde dairy ewes (Ayadi et al, 2011). On the other hand, the percentages of cisternal milk in the current study were lower than those percentages in Lacuane (74-77%, Rovai et al, 2002;Castillo et al, 2009) and Sarda ewes (82%, Nudda et al, 2000).…”
Section: Discussionsupporting
confidence: 69%
“…The increased milk protein content during lactation was in agreement with the results obtained by Gargouri et al (1993) and Ayadi et al (2014), who found that milk protein content during the suckling period was lower than in the milking period. The average milk fat percentage (4.41%) in this trial was similar to the value reported by Abd Allah et al (2011) in Chios ewes and Ayadi et al (2014) in Najdi ewes, but was lower than the values (6.2-7.4%) reported by Nudda et al (2002) in Awassi ewes and Castillo et al (2009) in Lacaune and Manchega ewes. Breed differences and diet could explain the discrepancies in fat percentages between these results and those of previous studies.…”
Section: Resultssupporting
confidence: 55%
“…According to Marnet (1997), the decrease in milk yield during weaning might be explained by the reduced emptying frequency and to a lesser degree by dam-lamb separation. When extended emptying intervals were practised, alveolar drainage decreased and intramammary pressure increased, all of which had negatively affected milk secretion, and eventually could have decreased milk yield (Castillo et al, 2009). The inconsistencies in daily milk yield dropping rates in this trial compared with other studies are probably due to the milking management, breed differences, and variation in cisternal size.…”
Section: Resultscontrasting
confidence: 37%
“…Cistern size is an important factor in determining the milkability (L abussière, 1988; Marnet and McKusick, 2001) and the adequate interval between milkings (Knight and Dewhurst, 1994;Salama et al, 2003). Animals that store a large proportion of milk in the gland cistern produce more milk, and are more able to tolerate extended milking intervals (Salama et al, 2004;Castillo et al, 2008b;Castillo et al, 2009). Moreover, cistern size plays an important role in controlling milk secretion because when the cistern reaches its full capacity, physical pressure and FIL concentration within alveoli are increased (Wilde et al, 1996).…”
Section: Introductionmentioning
confidence: 99%